Association of incident gabapentin use: with long-term use of opioids, benzodiazepines and Z-drugs - Bjarni Páll Linnet Runólfsson 1996- (2023)
Gabapentin was originally approved for treatment of seizures in patients with epilepsy and has also been used for neuropathic and inflammatory pain. In addition, off-label use has increased for various disorders, including mental disorders, such as anxiety disorders and bipolar disorders as well as chronic back pain. Gabapentin prescriptions have increased markedly in recent years in the United States and in the United Kingdom. Recent studies suggest that gabapentin is misused when taken with other drugs, such as opioids, benzodiazepines (BZD) and Z-drugs. Although gabapentin is considered safe when used alone, concomitant use with the aforementioned drugs is dangerous and increases the risk of overdose. The aim of this research was to investigate the association between long-term use of opioids, BZD and Z-drugs and incident gabapentin use. The study included persons who contacted services of the Primary Health Care of the Capital Area in Iceland from January 2009 to December 2012. Information medical diagnoses (ICD-10 codes) were retrieved from the medical records database of the Primary Health Care of the Capital Area. Data on prescriptions for opioids, BZD and Z-drugs were obtained from the Prescription Medicines Register at the Directorate of Health. The subjects in the study were divided into four groups with respect to long-term (continous for three-years) use of defined daily dose (DDD) of opioids, BZD and Z-drugs and the incidence rate ratio (IRR) of gabapentin was assessed using Cox regression. The effect of certain chronic conditions and long-term use of SSRI drugs was also explored. Finally, the magnitude and duration of future gabapentin use was examined. The results showed that long-term use of opioids, BZD or Z-drugs was associated with increased risk of future gabapentin use. Individuals using opioids and equal or over 30 DDDs of BZD or Z-drugs were most likely to initiate gabapentin therapy (IRR 7.42; 95% CI 6.69-8.22). These individuals also had the longest average duration of future gabapentin ...